Phosphorylation of Huntingtin by Cyclin-Dependent Kinase 5 Is Induced by DNA Damage and Regulates Wild-Type and Mutant Huntingtin Toxicity in Neurons - Anne, Sandrine L. (J Neurosci, 2007)
Huntingtin is an antiapoptotic protein that becomes toxic when its polyglutamine stretch is expanded, resulting in Huntington's disease (HD). Protein context and posttranslational modifications regulate huntingtin toxicity. Identifying signaling pathways that act on huntingtin is, therefore, key to understanding huntingtin function in normal and pathological conditions. We show here that huntingtin is phosphorylated by the cyclin-dependent kinase 5 (Cdk5) at serines 1181 and 1201. Phosphorylation can be induced by DNA damage in vitro and in vivo. The state of huntingtin phosphorylation is a crucial regulator of neuronal cell death. Absence of phosphorylation of huntingtin at serines 1181 and 1201 confers toxic properties to wild-type huntingtin in a p53-dependent manner in striatal neurons and accelerates neuronal death induced by DNA damage. In contrast, phosphorylation at serines 1181 and 1201 protects against polyQ-induced toxicity. Finally, we show in late stages of HD a sustained DNA damage that is associated with a decrease in Cdk5/p35 levels. We propose that wild-type huntingtin is a component of the DNA damage response signal in neurons and that the Cdk5/DNA damage pathway is dysregulated in HD.